2006
DOI: 10.1038/sj.onc.1209695
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Fer induces PP1 activation and cell-cycle arrest in malignant cells

Abstract: Fer is a nuclear and cytoplasmic intracellular tyrosine kinase. Herein we show that Fer is required for cell-cycle progression in malignant cells. Decreasing the level of Fer using the RNA interference (RNAi) approach impeded the proliferation of prostate and breast carcinoma cells and led to their arrest at the G0/G1 phase. At the molecular level, knockdown of Fer resulted in the activation of the retinoblastoma protein (pRB), and this was reflected by profound hypo-phosphorylation of pRB on both cyclindepend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 57 publications
2
44
0
Order By: Relevance
“…Interestingly, Nir and colleagues have reported a role for FER in the proliferation of breast carcinoma and prostate cell lines. 29 In our study, we found that some AML cell lines and fresh AML blasts have activated FES and/or FER. Therefore, the activation status and the requirement for FES kinases should be investigated downstream of other oncogenic tyrosine kinases.…”
Section: Activation Of Fes Kinases In Aml E Voisset Et Almentioning
confidence: 70%
“…Interestingly, Nir and colleagues have reported a role for FER in the proliferation of breast carcinoma and prostate cell lines. 29 In our study, we found that some AML cell lines and fresh AML blasts have activated FES and/or FER. Therefore, the activation status and the requirement for FES kinases should be investigated downstream of other oncogenic tyrosine kinases.…”
Section: Activation Of Fes Kinases In Aml E Voisset Et Almentioning
confidence: 70%
“…The kinase was detected in all human malignant cell lines analyzed (20,21), and its levels in malignant prostate tumors are significantly higher than those detected in benign growths (22). Furthermore, downregulation of Fer impairs the proliferation of prostate, breast, and colon carcinoma cells (23), induces death in colon carcinoma and non-small cell lung cancer (NSCLC) cells (24,25), abolishes the ability of prostate carcinoma PC3 and V-Sis-transformed cells to form colonies in soft agar (22), and prevents the metastatic spread of breast and lung adenocarcinoma tumors (26,27). At the clinical level, high Fer expression levels have been linked to poor prognosis of hepatocellular carcinoma (HCC; ref.…”
Section: Introductionmentioning
confidence: 96%
“…In addition, the stable downregulation of Fer using antisense cDNA impairs PC-3 cell growth and colony formation in vitro (11). RNA interference against Fer similarly inhibits cell proliferation, causing a G 0 -G 1 cell cycle arrest via the retinoblastoma protein, cyclindependent kinases (CDK4 and CDK2), and phosphatase PP1a (15).…”
Section: Introductionmentioning
confidence: 99%